ANALISIS PENGARUH INFRASTRUKTUR EKONOMI TERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA - Eko Fajar Cahyono (Jurnal Ekonomi Pembangunan, 2012)
This research intent to measure one how far public infrastructure influence as highway, electricity,fresh water and telephone and seluler to Gross Domestic Product at Indonesia. This research goes upon on classic economic growth theory and neoklasik what does look on that infrastructure constitutes associate physical capital good direct and indirect to economic growth. This research utilize analisis's method bifilar linear regression and time series's data. Base estimation result is found that infrastructure publicing to have influence that signifikan and terhdap's positive Gross Domestic Product.